Age-based Marketing Practices and Young People as Economic Actors in the Mobile Telephony Market in Provincial Vietnam - Huijsmans, Roy (Makara Human Behavior Studies in Asia, 2021)
In this article, I conduct an analysis of age-based marketing strategies employed by network providers and present insights obtained from mobile phone history interviews with young people in provincial Vietnam. From these data I argue that young people are a perpetual demographic market frontier in the commercialized mobile media landscape of Southeast Asia. I indicate how network providers contribute to shaping contemporary childhood and youth with their age-based marketing strategies. However, young people’s navigation of the commercial terrain of competing network providers is not determined by commercial forces solely but is also informed by various non-economic factors. This article finds that an appreciation of young people as consumers in the mobile phone era requires appreciating the powerful influence of network providers as well as the multiple relationships in which their economic decision-making is embedded.